Real world evidence on gemcitabine and nab-paclitaxel combination chemotherapy in advanced pancreatic cancer - Blomstrand, Hakon (BMC Cancer, 2019)
BACKGROUND: In the recent phase III trial MPACT the combination of gemcitabine and nab-paclitaxel (Gem/NabP) showed increased overall survival compared to gemcitabine alone in the treatment of advanced pancreatic ductal adenocarcinoma (aPDA). Until now there has been limited information on the clinical benefit and toxicity of the combination regimen in a real world setting. In addition the value for patients with locally advanced rather than metastatic aPDA has been unclear, since the former category of patients was not included in the MPACT trial. METHODS: A multicentre retrospective observational study in the South Eastern Region of Sweden was performed, with the first 75 consecutive patients diagnosed with aPDA (both locally advanced and metastatic disease) who received first-line treatment with Gem/NabP. RESULTS: In the overall population median progression free survival (PFS) and overall survival (OS) were 5.2 (3.4–7.0 95% CI) and 10.9 (7.8–14.0 95% CI) months, respectively. Patients with metastatic disease displayed a median OS of 9.4 (4.9–13.9) and a median PFS of 4.5 (3.3–5.7) months whereas the same parameters in the locally advanced subgroup were 17.1 (7.6–26.6) and 6.8 (5.2–8.4) months, respectively. Grade 3–4 hematologic toxicity was recorded: Neutropenia, leukopenia, thrombocytopenia, and anaemia were observed in 23, 20, 5, and 4% of patients, respectively. Dose reductions were performed in 80% of the patients. CONCLUSION: This study confirms the effectiveness and safety of first-line Gem/NabP in both locally advanced and metastatic PDA in a real world setting. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-5244-2) contains supplementary material, which is available to authorized users.